ANALISIS STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syarifuddin; Purba, Mortigor Afrizal (LPPM Universitas Putera Batam, 2022)
This study plans to examine the impact of capital structure on profitability. Thisstudy has 15 samples of property and real estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period using purposive sampling technique. In this review, the capital structure is estimated using the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) proportions followed by Profitability using the ROA proportion. The analysis method of this study was reviewed using multiple linear regression tests using SPSS Version 25. From the analysis results showed that the Capital Structure variable (DAR and DER) partially had a significant effect on ROA Properties and Real Estate on the IDX for the 2016-2020 period at the level of significance less than 5%. Based on the results of hypothesis testing, it shows that simultaneously there is a significant effect between the variables DAR, DER (Capital Structure) on the ROA (Profitability) of Property and Real Estate companies for the 2016-2020 period listed on the IDX.